A new ratiometric fluorescent probe for detecting endogenous HClO in living cells. (29th January 2018) - Zhang, Li-Jie; Ning, Jun-Ya; Miao, Jun-Ying; Liu, Jin-Ting; Zhao, Bao-Xiang
Abstract : A new benzimidazole-hemicyanine-based ratiometric fluorescent probe (ZBM-H ) was developed, which showed high selectivity and sensitivity for detecting HClO. Abstract : A new benzimidazole-hemicyanine-based ratiometric fluorescent probe (ZBM-H ) was developed, which showed high selectivity and sensitivity for detecting HClO. Furthermore, ZBM-H with a longer wavelength emission (653 nm), good membrane permeability and less cytotoxicity was successfully used to image the exogenous and endogenous HClO in RAW264.7 cells.